GAMBARAN TOKOH WALISONGO DALAM BABAD TANAH JAWI - Ahwan Fanani; Ashabul Kahfi (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Walisongo figures are well-known as preachers of Islam in Java. They lived in 15th until 16th Century. Their story is popular through oral tradition as well as Javanese literature, one of which is Babad Tanah Jawi. The record of Walisongo in Babad Tanah Jawi cannot be separated from the function of Babad literature as legitimate source for Mataram Power. This article seeks to reveal the description of several Walisongo figures in Babad Tanah Jawi. The article employs literature study as starting point and focuses on intrinsic reading of Babad Tanah Jawi text. Walisongo figures are commonly depicted as protagonists in Babad Tanah Jawi, but Sunan Kudus is portrated quite antagonistic due to his support to Arya Penangsang whose position is as enemy of Sultan Pajang, in which Mataram’s kings claimed to be the heirs of Pajang. Walisongo figures, especially Sunan Kalijaga, provide moral and spiritual legitimation to Mataram Dynasty. Walisongo figures repreresent Islamic support to Mataram Dysnasty as Islamic Kings who gain legitimation from supranatural power, instead of people democratic voices.